Cork and guar gum supplementation enhanced the buoyancy of faeces, and protease supplementation alleviated the negative effects of dietary cork on growth and intestinal health of tilapia, Oreochromis niloticus × O. aureus. (12th August 2019) - Yang, Hang; Li, Xiaoqin; Liang, Gaoyang; Xu, Zhen; Leng, Xiang Jun
Abstract: To evaluate the effects of dietary cork, protease and guar gum on growth, intestinal health and faecal floatability of tilapia, fine or coarse particle cork (0.45–0.60 mm, 0.60–0.83 mm) was included in diets at 0 (control), 20 g/kg, 30 g/kg and 40 g/kg, and then, 0.175 g/kg protease (P) and 3 g/kg guar gum (G) were supplemented to the 40 g/kg coarse particle diet individually or in combination (P + G). Tilapia with an initial body weight of 15.0 ± 0.5 g were fed one of the 10 diets for 60 days. The results showed that weight gain (WG), apparent digestibility coefficient (ADC) of dry matter (DM) and crude protein (CP), intestinal evacuation ratio, intestinal digestive enzyme activity (IDE) and villus height decreased, and floating faeces ratio increased with the increasing cork level in diets. At the same supplementation level, coarse particle groups showed significantly higher floating faecal ratio than fine particle groups ( p < .05). Dietary protease increased the WG, ADC of DM, IDE and villus height ( p < .05), and guar gum increased floating faecal ratio when compared to 40 g/kg coarse particle group ( p < .05). However, the ADC of DM, IDE and villus height of protease group were still inferior to those of control group ( p < .05). In conclusion, dietary cork increased the floating faeces ratio, and the coarse particles produced more floating faeces than fine particles. Moreover, the supplementation of guar gum in cork‐supplemented diet further increased the floating faeces ratio. However, dietary cork negatively affected the growth performance of tilapia, which could be partially alleviated by the supplementation of protease.